The reshaped min d Searle, the biblical writers, and Christ's blood - Williams-Tinajero, Lace Marie. (Biblical Interpretation Series, 2011)
A number of biblical scholars and theologians have had interest in speech act theory ever since J.L. Austin (1911-1960) outlined how a speaker can perform actions with words. John R. Searle has made a significant contribution to speech act theory after Austin by rooting his philosophy of language in the philosophy of mind; however, Searle's categories remain largely under or misrepresented in theological circles. In this book, the author works exclusively with Searle's categories to examine five NT texts on the 'blood-of-Christ' motif (Rom 3:25; Heb 9:12; John 6:52-59; Rev 1:5b-6; Rev 7:13-14). The main result is a broader understanding of Christ's blood in a literal sense rather than simply as a metaphor for his death.